2009
DOI: 10.1002/chem.200900853
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Aromatic Azido Reduction with Concomitant Aliphatic Azide Employing Al/Gd Triflates/NaI and ESI‐MS Mechanistic Studies

Abstract: Aluminium and gadolinium triflates catalyze the chemoselective reduction of aromatic azides to the corresponding amines in combination with sodium iodide. This mild chemoselective method has been applied to the synthesis of various aryl amines, C2-azido-substituted pyrrolo[2,1-c][1,4]benzodiazepines, and fused[2,1-b]quinazolinones by an intramolecular azido reduction tandem cyclization reaction. Interestingly, this methodology selectively reduces aryl azides with enhanced yields and proceeds in shorter reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…ESI-MS is increasingly popular as a method of establishing solution speciation in organometallic reactions. [17][18][19][20][21][22][23][24][25][26] It has been used on systems with inherently charged catalysts, 27,28 with neutral catalysts that become charged via oxidation 29 or protonation, 30 and with catalysts with deliberately charged ligands. 31,32 Use of charged substrates is somewhat rarer, 17,[33][34][35][36][37][38][39][40] as is continuous monitoring of reaction solutions, but we favour this approach thanks to the complete picture of speciation it provides.…”
Section: Introductionmentioning
confidence: 99%
“…ESI-MS is increasingly popular as a method of establishing solution speciation in organometallic reactions. [17][18][19][20][21][22][23][24][25][26] It has been used on systems with inherently charged catalysts, 27,28 with neutral catalysts that become charged via oxidation 29 or protonation, 30 and with catalysts with deliberately charged ligands. 31,32 Use of charged substrates is somewhat rarer, 17,[33][34][35][36][37][38][39][40] as is continuous monitoring of reaction solutions, but we favour this approach thanks to the complete picture of speciation it provides.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Although the role of I 2 in the mechanism is still largely unclear, it can be rationalized by assuming the formation of a triiodide ion by the known reaction of iodine with iodide ions. [30] We have analyzed the interaction between CeCl 3 ·7H 2 O and the NaI/I 2 combination by X-ray photoelectron spectroscopy, and observed that there is no direct interaction between the cerium(III) site and the triiodide ion. However, we believe that a chloro-bridged oligomeric structure [31] of CeCl 3 ·7H 2 O is more effectively broken [a] All reaction were carried out by irradiation in a PowerMax Cooling microwave oven with a mixture of 4a and reagent system at a given power for the selected times.…”
Section: Resultsmentioning
confidence: 99%
“…ESI is an interesting 'ion‐fishing' technique because it gently transfers preformed ions directly from solution to the gas phase 23. ESI‐MS (and its tandem version ESI‐MS/MS) is rapidly becoming the technique of choice for fast screening of intermediates directly from solution in chemistry and biochemistry27–30 and in high‐throughput screening of homogeneous catalysis reactions, providing hitherto unavailable chemical information to mechanistic studies 15, 18. In this context, we were interested in employing the on‐line ESI‐MS technique to trap and characterize the transient species that are involved in the synthetic route for isatin 1 , under Sandmeyer's conditions.…”
Section: Methodsmentioning
confidence: 99%